2015
DOI: 10.1103/physrevb.91.155307
|View full text |Cite
|
Sign up to set email alerts
|

Spinor stochastic resonance

Abstract: We report on noise-induced spin ordering in a collective quasiparticle system: spinor stochastic resonance. Synergetic interplay of a polarization-modulated signal and a polarization noise allows us to switch coherently between the two metastable states of a microcavity-polariton spin bistable system. Spinor stochastic resonance is demonstrated in a zero-dimensional GaAs based microcavity. The resonance behaviors of both the spin amplification and the signal-to-noise ratio are experimentally evidenced as a fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Having established that the laser noise is a possible way of coupling external noise to the polariton system, it is indeed possible that, for the right amount of noise, one would see an increase in the coherent response of the amplified modulated signal, rather than the expected decrease. As a matter of fact, stochastic resonance has been observed in polariton bistable systems [29,30]. It has been shown that, by applying in the input laser power a small amplitude modulation with frequency around 1 kHz, the stochastic resonance appears for a range of noise power (between 0.1 to 0.3 B) in the polariton system [29].…”
Section: B Time-resolved Experiments: Residence Time and Kramers Timementioning
confidence: 99%
See 1 more Smart Citation
“…Having established that the laser noise is a possible way of coupling external noise to the polariton system, it is indeed possible that, for the right amount of noise, one would see an increase in the coherent response of the amplified modulated signal, rather than the expected decrease. As a matter of fact, stochastic resonance has been observed in polariton bistable systems [29,30]. It has been shown that, by applying in the input laser power a small amplitude modulation with frequency around 1 kHz, the stochastic resonance appears for a range of noise power (between 0.1 to 0.3 B) in the polariton system [29].…”
Section: B Time-resolved Experiments: Residence Time and Kramers Timementioning
confidence: 99%
“…As a matter of fact, stochastic resonance has been observed in polariton bistable systems [29,30]. It has been shown that, by applying in the input laser power a small amplitude modulation with frequency around 1 kHz, the stochastic resonance appears for a range of noise power (between 0.1 to 0.3 B) in the polariton system [29]. Actually here we found that, for this amount of noise, the Kramers time is of the order of milliseconds, which is indeed around the modulation period, as expected for the observation of stochastic resonance [31].…”
Section: B Time-resolved Experiments: Residence Time and Kramers Timementioning
confidence: 99%
“…This effect is caused by the population of one polariton spin state that can induce a blue shift in the orthogonally polarized polariton branch [33]. Then, the overall competition between the excitation laser polarization, spinor interactions, and cavity anisotropy dictates the possible outcome of the multistability [28,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…The bistability and spinor multistability of a microcavity polariton have been extensively studied both theoretically [16][17][18][19][20][21][22] and experimentally [23][24][25][26][27][28][29][30][31][32]. It relies on exciting the microcavity using a laser blue detuned with respect to the lower polariton branch (LP) and to measure the transmitted laser intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, previous works have shown that zerodimensional (0D) confined polaritons are ideal systems to investigate the polariton bistability [33][34][35][36] and particularly * clauderic.ouellet-plamondon@epfl.ch its sensitivity to noise [36][37][38]. The former study showed that a symmetrical collapse of the polariton hysteresis loop occurs for increasing noise strength on the polariton population.…”
Section: Introductionmentioning
confidence: 96%